Analysis of ant's habitat in the Quran: potential of the adaptation for sustainable urban landscape design in Malaysia - Mohd Yunus, Mohd Yazid; Nangkula, Utaberta; Ismail, Nor Atiah; Mohd Isa, Nor Kalsum; Ismail, Sumarni (American-Eurasian Network for Scientific Information, 2015)
Majority of the urban dwellers will experience physical urban disarray of a climate change from the unsustainable urban landscape design. Urban landscape design concept and policies in Malaysia fail to produce optimal solution to the threat of climate change. This paper will try to reveal answer for unsustainable issues in urban landscape design via simulation of the Quranic verses on the habitats of ant. The appropriate and relevant verses of the Quran regarding habitat of ant gathered to develop a nine-component sustainable landscape design template. Those variables explored from the habitat of ants from the Quran are used to insert with integral do " s and don " ts of sustainable habitat design. The habitat of ants in the Quran describes the spatial articulations, behavioral and socio-ecological that appropriate to be embedded into sustainable landscape design. It is anticipated that through this paper we can understand an integration of spatial articulation and social components of urban landscape design of the framework give it a distinctive mosaic that most urban landscape design system lack. The study also will support urban landscape design preservation and conservation of urban habitat and ecosystem, low carbon emissions, low urban crime, security and safety, urban social responsibility and respect for human rights and pride.